Comparising Case Fatality Rate (CFR) of Covid19 Pandemic in South East Asia Countries - Herlina J. EL- Matury (Jurnal Inovasi Kesehatan Masyarakat, 2020)
COVID-19 is the infectious disease caused by the most recently discovered corona virus. This new virus and disease were unknown before the outbreak began in Wuhan, China, in December 2019. Case fatality rates (CFR) and recovery rates are important readouts during epidemics and pandemics. In this article, an international analysis was performed on the ongoing coronavirus disease 2019 (COVID-19) pandemic. Data were retrieved from accurate databases according to the user’s guide of data sources for patient registries, CFR and recovery rates were calculated for each country. A comparison of CFR between countries was observed for 28th April 2020. The confirmed case fatality ratio (CFR) is the total number of deaths divided by the total number of confirmed cases at one point in time. Within Southeasth Asia, the confirmed CFR, as reported by the Center for Strategic and International Studies (CSIS) is 2.3%, and RR is 25.02%. Singapore has the highest number of confirmed cases, but has CFR close to zero. Indonesia has the highest value of CFR 8.13%, and has value of RR 13.18% lower than Malaysia’s RR 67.63%. Indonesia’s confirmed Covid-19 cases are rising extremely rapidly, and it now tops the region in terms of deaths from the virus. Meanwhile, Vietnam, Kambodia, and Laos have no death of confirmed cases. Vietnam and Singapore have shown their ability to managed the pandemic with its promt and aggressive response, they have been hailed as a global public-health model.